2011
DOI: 10.1021/nn2005574
|View full text |Cite
|
Sign up to set email alerts
|

DNA Cage Delivery to Mammalian Cells

Abstract: DNA cages are nanometer-scale polyhedral structures formed by self-assembly from synthetic DNA oligonucleotides. Potential applications include in vivo imaging and the targeted delivery of macromolecules into living cells. We report an investigation of the ability of a model cage, a DNA tetrahedron, to enter live cultured mammalian cells. Cultured human embryonic kidney cells were treated with a range of fluorescently labeled DNA tetrahedra and subsequently examined using confocal microscopy and flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
465
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(484 citation statements)
references
References 47 publications
13
465
2
4
Order By: Relevance
“…DNA has been extensively employed as a biotechnological tool, with applications in different forms of genetic modification, such as gene therapy and silencing (Fichou and Gersbach 2016), in vaccine development (Aps et al 2016) and as vaccine adjuvants (Rozenfeld et al 2012), and even in the delivery of macromolecules (as hydrogels and DNA cages) (Campolongo et al 2010;Walsh et al 2011). In many of these applications, the DNA molecules used are either in the form of long and circular plasmids (see, for example, Aps et al 2016;Robinson-Hamm and Gersbach 2016) or as small linear oligonucleotides (Fichou and Férec 2006;Rozenfeld et al 2012).…”
Section: Dnamentioning
confidence: 99%
“…DNA has been extensively employed as a biotechnological tool, with applications in different forms of genetic modification, such as gene therapy and silencing (Fichou and Gersbach 2016), in vaccine development (Aps et al 2016) and as vaccine adjuvants (Rozenfeld et al 2012), and even in the delivery of macromolecules (as hydrogels and DNA cages) (Campolongo et al 2010;Walsh et al 2011). In many of these applications, the DNA molecules used are either in the form of long and circular plasmids (see, for example, Aps et al 2016;Robinson-Hamm and Gersbach 2016) or as small linear oligonucleotides (Fichou and Férec 2006;Rozenfeld et al 2012).…”
Section: Dnamentioning
confidence: 99%
“…34 More recently DNA origami nanoarrays were demonstrated stable in cell lysates. 35 DNA cage structures have also been demonstrated capable of entering live mammalian cells, 36 while DNA tubes or barrels have been demonstrated directable to specific cell types to which they can either deliver 37 or expose 31 their specific cargo.…”
mentioning
confidence: 99%
“…[72][73][74] Turberfield et al found that DNA tetrahedra could enter a mammalian cell with or without the need of a transfection reagent. The tetrahedral DNA cage remained its structural intactness in the cellular environment for at least 48 h. [75] Fan et al investigated the endocytotic internalization of a DNA tetrahedron and its subsequent intracellular transport. [76] The DNA nanocages mainly resided in the lysosomes after a rapid internalization, which would affect their functions as a delivery agent.…”
Section: In-vivo Cargo Deliverymentioning
confidence: 99%